The effect of COVID‐19 vaccine literacy on attitudes towards COVID‐19 vaccine among university students - Durmuş Iskender, Mahinur; Eren, Handan; Durmuş, Ayşenur (Wiley, 2023)
AbstractObjectiveUniversity students are a large group of the population who should be vaccinated to prevent the spread of the pandemic. This research aimed to determine the effect of COVID‐19 vaccine literacy on the attitudes towards the COVID‐19 vaccine among university students.MethodsThis descriptive and cross‐sectional study was conducted with 2384 university students via online survey in September and October 2021. ‘Demographic Information Form’, ‘COVID‐19 Vaccine Literacy Scale’, and ‘Attitudes towards the COVID‐19 Vaccine Scale’ were used to collect the data. Data were evaluated via descriptive statistics, independent group t‐test, ANOVA, Tukey HSD, and Pearson Correlation analysis.ResultsThe mean score on the COVID‐19 Vaccine Literacy Scale was 27.26 ± 6.49 (moderate). Demographic differences that significantly affected students' vaccine literacy scales included parents' education levels (lower levels of parental education associated with higher communicative/critical vaccine literacy). Health sciences students had more positive attitudes to the COVID vaccine than students of other disciplines. The higher the level of mother's education, the more positive the student's attitude towards the vaccine, and similarly the higher the student's socio‐economic background the higher the positive attitude towards the vaccine. Examination of the relationship between the vaccine literacy scale and the attitudes towards the vaccine showed low levels of correlation.DiscussionStudents who had parents of lower education levels may have more responsibilities for explaining vaccination to their parents, thus improving their communicative/critical vaccine literacy.ConclusionA vaccine literacy scale with separate functional literacy score and critical/communicative score helps to explain some of socio‐demographic differences in students' scores, and similarly for attitude towards the COVID‐19 vaccine (positive and negative attitude sub‐scales).
Keywords: COVID-19 Vaccines; Cross-Sectional Studies; Attitude; Universities; Humans; COVID-19; Students; 4. Education; 3. Good health